Manajemen Kurikulum dalam Upaya Peningkatan Mutu Pendidikan - Yuhasnil Yuhasnil (Alignment:Journal of Administration and Educational Management, 2020)
The research objective is to examine curriculum management in an effort to improve the quality of education. The method used is literature study. With the aim of seeing curriculum management in improving the quality of education through improving the quality of human resources. Efforts to improve the quality of education must be supported by all parties, including managers of educational institutions at the central, regional and school levels including in the classroom. In the implementation of decentralized education in the era of regional autonomy, each region should have its own quality improvement curriculum design which is an elaboration or implementation of the education curriculum set by the center. This is in accordance with the demands of the curriculum, where both local governments and even lower levels (schools) are given the freedom to describe quality improvement programs so that in the future each region competes with each other for the advancement of education in their respective regions. Keywords: Curriculum Management, Education Quality, Human Resources